2003
DOI: 10.1074/jbc.m210852200
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Cellular Functions of Annexin XI Using Recombinant Human Annexin XI-specific Autoantibodies Cloned by Phage Display

Abstract: Functional studies of cellular proteins are often complicated by the lack of well-defined monoclonal antibodies, the production of which is hampered by the highly conserved nature of these cellular proteins across species. Annexin XI, a member of the Ca 2؉ -dependent, phospholipid-binding protein family, is an example of such a protein and was used in studies to devise a strategy using human autoimmune phage display libraries to generate reagents for biological studies of conserved cellular proteins. An IgG ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…8,9 There have been several functions suggested for ANXA11 in calcium signalling, cell division, apoptosis and exocytotic pathway. 10 Nevertheless, the data on the role of ANXA11 in human diseases have been limited; for example elevated ANXA11 protein levels were reported in colorectal cancer tissue correlated with tumour stage and poorer survival. 11 Autoantibodies against ANXA11 (identical to the '56K autoantigen') were identified in patients with autoimmune diseases such as rheumatoid arthritis, systemic lupus erythematosus, systemic sclerosis and antiphospholipid syndrome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 There have been several functions suggested for ANXA11 in calcium signalling, cell division, apoptosis and exocytotic pathway. 10 Nevertheless, the data on the role of ANXA11 in human diseases have been limited; for example elevated ANXA11 protein levels were reported in colorectal cancer tissue correlated with tumour stage and poorer survival. 11 Autoantibodies against ANXA11 (identical to the '56K autoantigen') were identified in patients with autoimmune diseases such as rheumatoid arthritis, systemic lupus erythematosus, systemic sclerosis and antiphospholipid syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…However, the wild-type ANXA11 protein and its R230C variant did not differ in terms of sensitivity to Ca2 þ in the recent study. 14 Besides a role in calcium signalling, annexin A11 has been implicated in apoptosis and vesicle trafficking, 8 cell growth, 10 survival of cancer cells 11 and terminal phase of cell division. 15 In this context, the development and maintenance of granulomatous inflammation in sarcoidosis have repeatedly been associated with impaired apoptosis of activated inflammatory cells.…”
Section: Resultsmentioning
confidence: 99%
“…Annexin A11 is implicated as being involved in cell growth (Farnaes and Ditzel, 2003) and a reduction in annexin A11 expression using RNAi stops cell division (Tomas et al, 2004). However, annexin A11 expression was decreased in metastasis, suggesting further dysregulation of this protein with tumour progression and possibly indicating that the tumour microenvironment plays a role in regulating annexin A11, although the specific mechanisms regulating this annexin remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not study the interaction between tropomyosin and S100A6 here, it is possible that the loss of motility observed after S100A6 depletion is caused, at least in part, by an involvement of S100A6 with tropomyosin. Annexin 11 is widely expressed and roles in cell division (Farnaes and Ditzel, 2003) and cytokenesis (Tomas et al, 2004) have been reported. The binding of annexin 11 to S100A6 has been shown to take place in the nuclear envelope (Tomas and Moss, 2003), where the complex may have a function in membrane deconstruction during nuclear envelope breakdown in mitosis.…”
Section: Discussionmentioning
confidence: 99%